(untitled) (American Journal of Islam and Society, 2014)
The International Institute of Islamic Thought (IIIT) organized a two-day series of intellectual panels at the Islamic Society of North America’s (ISNA) 50th annual convention, held in Washington, DC, over the Labor Day weekend (Aug. 31–Sept. 1, 2103). These events were hosted in the institute’s hospitality suite on the main floor of the Washington Convention Center. Recently published IIIT books and other selected publications were prominently displayed. A documentary on IIIT and its goals was shown before each session.